Catheter-associated recurrent intracardiac thrombosis and factor V Leiden mutation in a child with non-Hodgkin’s lymphoma - Corapçioğlu, Funda; Uysal, Kamer Mutafoğlu; Silistreli, Erdem; Unal, Nurettin; Oren, Hale; Açikel, Unal (The Turkish Journal of Pediatrics, 2005)
Patients with cancer have an increased risk for thromboembolism, which might be related to several factors including central venous catheters and chemotherapeutics. Congenital prothrombotic risk factors might also contribute to thrombotic events. In this report, we present a catheter-related recurrent intracardiac thrombosis in a boy with non-Hodgkin’s lymphoma and factor V Leiden mutation. Screening for factor V Leiden mutation in children with cancer and recurrent thrombotic events is recommended. Periodic echocardiography may be considered for a group of patients if the catheter tip is in the right atrium and therapy includes L-asparaginase and corticosteroids.